Antibacterial Activity of The Nucleoside Antibiotic (NA) Isolated from Streptomyces alboflavus - T.K. Aldaly, Zainab (University of Thi-Qar Journal of Science, 2011)
During this study a new antibiotic was isolated from Streptomyces alboflavus which was active against Gram-positive and Gram-negative bacteria .The isolate antibiotic waswhite crystalline powder at (28-30)C˚. Physicochemical properties were studied includesTLC, IR spectroscopy and Uv spectrum as well as color tests, all these studies indicate thatthe antibiotic produced by Streptomyces sp. Is a nucleoside antibiotic and gave the name(NA).The minimal inhibitory concentration of produced nucleoside antibiotic weredetermined against five standard gram positive positive and gram negative bacteria withMIC value ranged (2-25) µ/ml .